Assessment of anthelmintic efficacy of mebendazole in school children in six countries where soil-transmitted helminths are endemic. - Bruno Levecke; Antonio Montresor; Marco Albonico; Shaali M Ame; Jerzy M Behnke; Jeffrey M Bethony; Calvine D Noumedem; Dirk Engels; Bertrand Guillard; Andrew C Kotze; Alejandro J Krolewiecki; James S McCarthy; et al. (Public Library of Science (PLoS), 2014)
Robust reference values for fecal egg count reduction (FECR) rates of the most widely used anthelmintic drugs in preventive chemotherapy (PC) programs for controlling soil-transmitted helminths (STHs; Ascaris lumbricoides, Trichuris trichiura, and hookworm) are still lacking. However, they are urgently needed to ensure detection of reduced efficacies that are predicted to occur due to growing drug pressure. Here, using a standardized methodology, we assessed the FECR rate of a single oral dose of mebendazole (MEB; 500 mg) against STHs in six trials in school children in different locations around the world. Our results are compared with those previously obtained for similarly conducted trials of a single oral dose of albendazole (ALB; 400 mg).The efficacy of MEB, as assessed by FECR, was determined in six trials involving 5,830 school children in Brazil, Cambodia, Cameroon, Ethiopia, United Republic of Tanzania, and Vietnam. The efficacy of MEB was compared to that of ALB as previously assessed in 8,841 school children in India and all the above-mentioned study sites, using identical methodologies.The estimated FECR rate [95% confidence interval] of MEB was highest for A. lumbricoides (97.6% [95.8; 99.5]), followed by hookworm (79.6% [71.0; 88.3]). For T. trichiura, the estimated FECR rate was 63.1% [51.6; 74.6]. Compared to MEB, ALB was significantly more efficacious against hookworm (96.2% [91.1; 100], p<0.001) and only marginally, although significantly, better against A. lumbricoides infections (99.9% [99.0; 100], p = 0.012), but equally efficacious for T. trichiura infections (64.5% [44.4; 84.7], p = 0.906).A minimum FECR rate of 95% for A. lumbricoides, 70% for hookworm, and 50% for T. trichiura is expected in MEB-dependent PC programs. Lower FECR results may indicate the development of potential drug resistance.